Photoreduction of carbon dioxide and methane to formate, acetate derivatives and hydrogen over immobilized titania nanoparticles and nitrogen-doped titania nanotube arrays - Delavarii, Saeed (2017)
The major causes of global warming are mainly attributed to greenhouse gases such as carbon dioxide (CO2) and methane (CH4). The conversion of the gases to renewable fuels has stirred interest for greenhouse gas mitigation and energy crises alleviations. The main objective of this study was to develop the nanosized titania (TiO2) catalyst for selective CO2 and CH4 reduction to fuels by using photoreactor. The photoreduction of CO2 in the presence of CH4 was studied over immobilized titania nanoparticles on stainless steel mesh. Response surface methodology was used to assess individual and interactive effects of important parameters on conversion. Calcination of coated titania nanoparticles increased the absorption of ultraviolet-visible light while uniform photocatalyst structure commensurate with decreasing agglomeration. The observed maximum conversions were 37.9% and 48.7% for CO2 and CH4, respectively. It is apparent that the optimization exercise is more efficient with response surface methodology. The corresponding products selectivity were 4.7%, 4.3%, 3.9%, 41.4% and 45.7% for ethane, acetic acid, formic acid, methyl acetate and methyl formate, respectively. The performance of highly ordered nitrogen-doped titania nanotube arrays were then fabricated by anodization method, used for photoreduction of CO2 and CH4. Field emission scanning electron microscopy images of titania nanotube arrays indicated highly ordered and vertically oriented morphology with inside diameter ranging from 3 to 50 nm. Optimum experimental conditions indicated that maximum CO2 and CH4 conversion could reach up to 41.5% and 62.2%, respectively. Correspondingly, hydrogen at selectivity of 80.5% and several by-products including carbon monoxide and hydrocarbons such as ethane, propane and ethylene were produced from photoreduction. The quantum efficiency of the photoreactor with immobilized titania nanoparticles coated on stainless steel meshes for methyl formate and methyl acetate were 0.163% and 0.147%, respectively. Furthermore, the quantum efficiency of the photoreactor with nitrogen-doped titania nanotube arrays synthesized by electrochemical anodization method, for hydrogen was 0.294%. Finally, kinetic model using Langmuir-Hinshelwood developed to investigate photocatalytic reduction process, was found to fit well with theexperimental data. In conclusion, photoreactor with nitrogen doped titania nanotube arrays increased CO2 and CH4 reduction to fuels as much as 1.7 times.